The Relationship between Organizational Commitment and Job Satisfaction - Yeşim Avunduk (Journal of Educational Issues, 2024)
The study aimed to determine the relationship between organizational commitment and job satisfaction of individuals working in the sports sector. The sample of the study consisted of a total of 496 people (375 males and 121 females), who were working in a private company operating in the sports sector in Istanbul, and selected by easy sampling method. In addition to the personal information form, the “Organizational Commitment Scale” developed by Meyer and Allen (1984, 1997) and adapted to Turkish by Boylu et al. (2007), and the Minnesota Job Satisfaction Scale, developed by Weiss et al. (1967) and adapted into Turkish by Baycan (1985) were used as data collection tools. Analyzes were analyzed using SPSS 22.0 package program. Independent t-test, ANOVA and Pearson Correlation analyses were performed to analyse the data. In addition, the analyzes were performed at a 95% confidence interval. Analysis results showed that there was a significant difference in the continuance commitment sub-dimension of individuals according to the gender variable. It was determined that there was a significant difference in both the job satisfaction levels and the affective and normative commitment levels of the individuals according to their welfare status. Moreover, it was determined that there was a significant difference in all sub-dimensions of the job satisfaction scale and in all sub-dimensions of the organizational commitment scale according to the educational status of the participants. As a result, it was determined that there was a positive and moderate relationship between “Affective Commitment” and “Continuance Commitment” and “Internal Satisfaction” and “External Satisfaction”. Another result, it was determined that the organizational commitment and job satisfaction levels of the individuals differed according to their socio-demographic characteristics, and as the affective and continuance commitment of the individuals increased, their job satisfaction increased.